DESIGN VIDEO PROFILE BASED MULTIMEDIA AUDIO VISUAL AND BROADCASTING AS A MEDIA PROMOTION - Lusyani Sunarya; Putri Apryllia; Siti Isnaini (CCIT Journal, 2016)
The development of media campaign currently very rapid. Media campaign that is widely used today not only in the form of visual communication media, but many companies that develop the promotion through audio-visual media. The development of the hospitality world increasingly rapidly, causing more and more facilities and advantages that should be promoted in order to compete, especially at Padjadjaran Suites Busines & Conference Hotel. The aim of this study was to design-based audiovisual media in order to become an effective appeal, especially in the delivery of information and promotion of it - matters relating to the overall Padjadjaran Suites Busines & Conference Hotel. Padjadjaran Suites Business & Conference Hotel is a four star hotel located in Tangerang. Existing problems that the media used by Padjadjaran Suites Business & Conference Hotel is in the form of visual communication media, in general, people are more receptive to information through interactive media and communicative, so Padjadjaran Suites Business & Conference Hotel requires video media profile as a medium for supporting information and promotion at the show to prospective customers, establish relationships with clients, or as a medium of information to the public, so that the design of video media profile that show the entire scope, advantages and facilities of the hotel, could be a solution in solving problems in media promotion and information. The methods used in this research is a method of analysis of the problems, methods of data collection, data analysis, methods of analysis, as well as the basic concepts of media production. In the basic concepts of media production there are stages of preproduction, production, and postproduction. The end result of this design is a video that can be directly used for media promotion.